2018
DOI: 10.1097/mcg.0000000000000676
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease is Misdiagnosed Based on Serology Only in a Substantial Proportion of Patients

Abstract: Background: Although the diagnostic process in celiac disease (CeD) has been addressed in several international guidelines, little is known about the actual proceeding in current clinical practice. This study investigated the initial presentation, the diagnostic process, follow-up evaluations, and adherence to a gluten-free diet in CeD patients in a real-life setting in Switzerland from a patient’s perspective. Methods: We performed a large patient surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…In the present study, most of the overlapped diagnoses of CD with NCGS or WA were physician-diagnosed cases (6 out of 8), but only one of the cases reported that a gastroenterologist diagnosed her/his condition (NCGS). Assessing CD by non-specialist physicians is sometimes based on celiac serology only [22], but the prevalence of positive serology is almost three-fold higher than the prevalence of CD based on a formal diagnosis [23]. At the moment, the instrument utilized did not inquire about the diagnostic procedures of the GRDs reported by the participants.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, most of the overlapped diagnoses of CD with NCGS or WA were physician-diagnosed cases (6 out of 8), but only one of the cases reported that a gastroenterologist diagnosed her/his condition (NCGS). Assessing CD by non-specialist physicians is sometimes based on celiac serology only [22], but the prevalence of positive serology is almost three-fold higher than the prevalence of CD based on a formal diagnosis [23]. At the moment, the instrument utilized did not inquire about the diagnostic procedures of the GRDs reported by the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Les manifestations cliniques de la MC sont très diverses et la polysérite est exceptionnellement décrite et n’a jamais été rapportée comme révélatrice de la MC jusque-là. La maladie est révélée généralement de manifestations essentiellement digestives selon une récente cohorte Suisse de 1689 patients avec toutefois 1,8% des patients complètement asymptomatiques [ 3 ].…”
Section: Discussionunclassified
“…Even if the diagnostic criteria for CD are very clear and the interest of patients and medical specialists in CD has been growing worldwide, the problem of diagnostic errors in CD is still remarkably relevant in clinical practice, as suggested by the large body of published papers on this topic in the last twenty years [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. It has been reported that about 20% of coeliac patients are currently unrecognized and diagnoses are still burdened by a significant diagnostic delay [ 21 , 40 , 51 , 54 , 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Coeliac Diseasementioning
confidence: 99%
“…On the other hand, a negative testing for HLA DQ2 and DQ8 has a negative predictive value of nearly 100% [ 36 , 104 ]. However, in our clinical experience and the reported literature, false positive diagnoses of CD can occur on the basis of a genetic test showing HLA DQ2.5 or HLA-DQ8 molecules [ 53 ]. Only rarely a true diagnosis of CD was missed because of wrong interpretation of HLA-DQ2.2 or HLA-DQ7.5.…”
Section: Coeliac Diseasementioning
confidence: 99%